Tendinţe actuale ale gospodăriilor populaţiei din România - Stanciu, Mariana (Calitatea Vieții, 2017)
The modernization of the dominant way of life, in the context of the continuous change of the global society and economy, strongly influenced the structuring of the European households, during the last 2-3 decades. Romanian society has been influenced in this direction too, even if, in some aspects, in a different manner in comparison with the European context. An important effect of the European process of social modernization was the rising of the households number. This thing is not valuable for Romania, where the number of households decreased, in spite of the rising numbers of buildings and houses. The migration phenomenon played a decisive role in the European and world changing, Romania becoming a country of massive emigration. However, many signs of way of life modernization appeared in Romania too, for instance, the rising number of the one member households. But as regards education, Romania seems to be back in the history, registering again 245 400 persons affected by illiteracy (in 2011). This article creates a proper framework for understanding social changes, starting from some objective social indicators concerning the dynamics of Romanian households during the last two decades. Such an approach might contribute to the better informed decisions of the public policy makers.